Do IGF1 Polymorphisms Really Matter for Fertility? - Veiga, Rafaela Nasser; Silva, José Samuel Da; Gelmini, Georgia Fernanda; Schuffner, Alessandro; Bicalho, Maria Da Graça (Archives of Clinical and Biomedical Research, 2023)
Our aim was to investigate the possible association between IGF1 gene, fertility and implantational success. A case-control study has been conducted with a patient sample of 49 unrelated Brazilian couples who underwent assisted techniques due to idiopathic infertility, and 123 control fertile couples. After DNA extraction from the peripheral blood by saltingout method, exons 3, 4 and 5 of IGF1 gene, as well as their flanking regions, were amplified by PCR. Genetic variability was evaluated by Sequence Base Typing (SBT). Possible associations were estimated by binary logistic regression models. Thirteen allelic variants were found in IGF1 gene, but only three of these loci were considered polymorphic. These SNPs were rs5742620 (C > A), rs2072592 (G > A) and rs11111267 (T > C), in intronic regions. Although this study could not find an association between IGF1 and infertility, a possible association cannot be ruled out, due to the complex network regarding reproduction process. The higher frequency of rs11111267(C) in male patients is very suggestive that this SNP may play a role in male fertility and deserves further investigation. Genetic variation in intronic regions of the IGF1 might alter the gene expression level which may impact gametogenesis, embryo implantation and zygote development.